Historical and legal description of concept «air lines» - Тимкович, Ірина Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The author of the article notes that the first airline considered air route Paris-London-Paris, opened in late 1918. Actually international air began to develop in 1919 after the conclusion of the Paris Convention for the aeronautical airservices between the countries of the world. It is emphasized that the present state of Civil Aviation of Ukraine on the use of airspace of our country for the purpose of air transport and aerial work performance influenced the formation of national legislation in the field of operations of the routes. But also in the regulations fixing concepts routes, aircraft line airways, causing airservices need to study their content and value together. So the goal of the article is to conduct historical and legal description of what constitutes "airline" comparative analysis of other concepts set out by international and national laws that are similar in nature. The author concluded that the availability of a wide array of conceptual apparat usin the regulation of the use of airspace for the implementation of airtransport and aerial work execution, which requires a clear and consistent normalization them. The refore, the proposed development and approval by he competent authority of the unified directory of definitions of specialized terms that have regulatory force. It appears that in the future a conceptual device used to improve air legislation of Ukraine, including the operation of routes, identif ingkeytrends shaping and implementing public policy in this area, to avoid contradictions in the conceptual apparatus for competitive access carriers in the market of air transportation.